Oil and gas production technology - Toporov, V.; Dobrunov, D. (National Technical University "Kharkiv Polytechnic Institute", 2018)
This training manual includes practical works on the course “Oil and gas production technology” in English. The petroleum industry include the global processes of exploration, extraction, refining, transporting (often by oil tankers and pipelines), and marketing petroleum products. The largest volume products of the industry are fuel oil, gasoline (petrol) and natural gas. The industry is usually divided into three major components: upstream, midstream and downstream. Upstream sector of petroleum industry includes exploration, development and production of crude oil or natural gas. Practical works acquaint students with the calculation methods of some processes and equipment used in the oil-gas production. The manual is intended for the students trained on a speciality 6.050304 "Oil and gas extraction" in English.